How Did Nickel Cobaltite Reinforced Carbon Microfibre Symmetrical Supercapacitor Fare Against A Commercial Supercapacitor?. (20th August 2017) - Chiam, S.L.; Lim, H.N.; Foo, C.Y.; Pandikumar, A.; Huang, N.M.
Abstract: Various types of supercapacitor electrodes have been reported, which include carbon materials, metal oxides, and conducting polymers. They have been subjected to electrochemical analyses using three- or two-electrode systems. The closest system to a real commercial application is the two-electrode system. Herein, we report the fabrication of a solid-state supercapacitor with nickel cobaltite reinforced carbon microfibre electrodes using two electrode system. This supercapacitor, called the NICAF, was compared to a commercial supercapacitor (KEMEX). The specific capacitances of NICAF and KEMEX were 124.21 F/g and 44.49 F/g at 1 A/g, respectively. The capacitance retention of NICAF was 93% after 900 galvanostatic charge/discharge cycles, whereas KEMEX was able to retain 99% after the same number of cycles. The energy and power densities of NICAF were 8.32 Wh/kg and 489.25 W/kg, respectively, while those of KEMEX were 2.07 Wh/kg and 409.45 W/kg, respectively. The life cycles of NICAF and KEMEX were verified and compared at three temperature ranges: 0, 30, and 60 °C. KEMEX exhibited superior cycle stability, with a capacitance retention of up to 99% in all temperature ranges, whereas NICAF performed optimally by recording up to 97% retention at 0 °C. However, the increase in temperature up to 30 °C reduced the stability to 93% and a further increase to 60 °C disrupted the stability test. Nevertheless, these extensive electrochemical analyses showed that the overall performance of NICAF was comparable to that of the commercially available KEMEX supercapacitor.